Voices at the margins: Nepali international students’ experiences and resilience in Denmark - Timsina, Nitya (Journal of International Students, 2025)
This study examines the experiences of Nepalese students pursuing higher education in Denmark, illuminating the distinct challenges they encounter as international students. Framed within the context of globalization, the research critiques the dominant, often homogenizing narrative of international student mobility, which centers on English-speaking nations and overlooks diverse cultural identities. These students encounter significant economic pressures, cultural isolation, and instances of societal prejudice, intensified by growing anti-immigrant sentiment across Europe. Drawing on Doreen Massey’s concept of space alongside the philosophies of Wittgenstein, Nietzsche, Heidegger, and others, the study challenges the notion of a singular international education experience and emphasizes the resilience of Nepalese women as they balance cultural values with academic pursuits in a foreign setting.